Sclerotinia Rot of Hygrophila auriculata (Schum.) Heynne. in Lateritic Zone of West Bengal, India - Mondal, Bholanath; Debbarma, Papiya; Khatua, Dinesh Chandra (International Journal of Bio-resource and Stress Management, 2016)
Sclerotinia rot of Kulekhara [Hygrophila auriculata (Schum.) Heynne.]caused by Sclerotinia sclerotiorum (Lib.) de Barywas recorded probably first time in a homestead gardens at Sriniketan (Birbhum district) under Lateritic-red agroclimatic zone of West Bengal, India during winter months of January-February, 2014 and 2015. Kulekhara is an Indian ayurvedic plant familiar for its medicinal value commonly used for increasing haemoglobin in blood. It is also used as vegetable in rural Bengal. S. sclerotiorum is one of the most devastating and cosmopolitan necrotrophic fungal plant pathogens having wide host range infects a numbers of economically important plants throughout the world. Initially water soaked lesions were produced on branches and leaves. Soon the affected area covered with white mycelial growth of the causal fungus. With progress of the disease, many plants died. Sclerotia formation was not found on the infected plants but more or less spherical large and black sclerotia were produced in soil at base of the infected plant. The pathogen did not show host specificity. PDA medium amended with chloramphenicol was used to isolate and maintain the pathogen. White mycelium with hyaline, branched and septate hyphae was produced by the pathogen on PDA medium. Black sclerotia near spherical in shape generally were formed within 4−6 days of incubation at 25 °C.